The Tao encounters the West : explorations in comparative philosophy - Li, Chenyang, 1956- (SUNY series in Chinese philosophy and culture., 1999)
The relation between liberal democracy and Confucianism is explored by author Chenyang Li as he argues for a Chinese future where both coexist as independent value systems. This relationship is shown through a comparative study of Chinese and Western ideas and philosophies of being, truth, language, ethics, religion, and values. The book covers a wide range of philosophers and philosophies, including Aristotle, Zhuang Zi, Heidegger, Confucius, Kripke, and feminist care ethics. Li shows how a comparative approach to different patterns of thinking in Chinese and Western traditions sheds light on the intelligibility of Chinese multiple ethico-religious practice, which in turn supports the claim that democracy and Confucianism can coexist as independent value systems.